Direct and cross-scheme effects in a research and development subsidy program - Hanna Hottenrott; Cindy Lopes-Bento; Reinhilde Veugelers (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2014)
This study investigates the effects of an R&D subsidy scheme on participating firms' net R&D investment. Making use of a specific policy design in Belgium that explicitly distinguishes between research and development grants, we estimate direct and cross-scheme effects on research versus development intensities in recipients firms. We find positive direct effects from research (development) subsidies on net research (development) spending. This direct effect is larger for research grants than for development grants. We also find cross-scheme effects that may arise due to complementarity between research and development activities. Finally, we find that the magnitude of the treatment effects depends on firm size and age and that there is a minimum effective grant size, especially for research projects. The results support the view that public subsidies induce higher additional investment particularly in research where market failures are larger, even when the subsidies are targeting development.
Keywords: H23; O31; O38; 330; R&D; Complementarity; Research Subsidies; Development Subsidies; Innovation Policy